2016
DOI: 10.1104/pp.15.01493
|View full text |Cite
|
Sign up to set email alerts
|

AtKC1 and CIPK23 Synergistically Modulate AKT1-Mediated Low-Potassium Stress Responses in Arabidopsis

Abstract: In Arabidopsis (Arabidopsis thaliana), the Shaker K + channel AKT1 conducts K + uptake in root cells, and its activity is regulated by CBL1/9-CIPK23 complexes as well as by the AtKC1 channel subunit. CIPK23 and AtKC1 are both involved in the AKT1-mediated low-K + (LK) response; however, the relationship between them remains unclear. In this study, we screened suppressors of low-K + sensitive [lks1 (cipk23)] and isolated the suppressor of lks1 (sls1) mutant, which suppressed the leaf chlorosis phenotype of lks1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 57 publications
2
58
0
Order By: Relevance
“…An interesting emerging case of a multifunctional CIPK is provided by CIPK23, which appears to represent a key master regulator of plant nutrient sensing and acquisition. This kinase has been reported to function in potassium and nitrate as well as iron, magnesium and ammonium homeostasis (Geiger et al ., ; Ho et al ., ; Maierhofer et al ., ; Scherzer et al ., ; Wang et al ., ; Behera et al ., ; Straub et al ., ) (Fig. ).…”
Section: The Ca2+ Decoding Toolkit In Plantsmentioning
confidence: 98%
“…An interesting emerging case of a multifunctional CIPK is provided by CIPK23, which appears to represent a key master regulator of plant nutrient sensing and acquisition. This kinase has been reported to function in potassium and nitrate as well as iron, magnesium and ammonium homeostasis (Geiger et al ., ; Ho et al ., ; Maierhofer et al ., ; Scherzer et al ., ; Wang et al ., ; Behera et al ., ; Straub et al ., ) (Fig. ).…”
Section: The Ca2+ Decoding Toolkit In Plantsmentioning
confidence: 98%
“…In addition, a silent Shaker channel α‐subunit AtKC1 is also expressed in guard cells, and can assemble with these four channels forming heteromeric K + channels (Duby et al ., ; Wang et al ., ; Jeanguenin et al ., ). AtKC1 behaves as a general modulator of Shaker K in channels, reducing channel conductance and negatively shifting the activation threshold of these K in channels (Duby et al ., ; Wang et al ., , ; Jeanguenin et al ., ). In rice, the Shaker channel genes OsKAT2 and OsKAT3 are expressed in guard cells, and the silent OsKAT3 could interact with and negatively regulate OsKAT2 channel activity (Hwang et al ., ; Moon et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it was predicted that KC1 interacted with CIPK23, TPK1 and KUP3 respectively, and CIPK23 also interacted with SOS1 and CBL4(SOS3) respectively ( Figure 6C). Given that the interaction between SOS1 and SOS3 [56], KC1 and CIPK23 [51,52], CBL4(SOS3) and CIPK6 [53] has been proved, thus the consistent expression and their interaction of SOS1, KC1, CIPK23, CBL4, CIPK6, KUP3, TPK1 in the network, provide new possible mechanisms for banana roots to response to potassium stress. In a word, the genes in profile 7 were mainly related to ion transport of potassium.…”
Section: Discussionmentioning
confidence: 95%
“…The results suggested that the CBL1/CBL9-CIPK23-AKT1 pathway was not involved in banana root system in response to potassium stress. AtKC1 is a K + channel regulatory subunit, which together with AtCIPK23, has been reported to coordinate the regulation of AtAKT1-mediated K + short stress response in Arabidopsis [51,52]. In addition, the CBL4/CIPK6 complex was revealed to modulating AKT2 activity in Arabidopsis [53].…”
Section: Discussionmentioning
confidence: 99%